Sensitivity of welfare effects estimated by equilibrium displacement model: A biological productivity growth for semisubsistence crops in Sub-Sahara African market with high transaction costs - Takeshima, Hiroyuki (International Food Policy Research Institute, 2009)
This paper discusses the application of the equilibrium displacement model (EDM) to estimate ex-ante the welfare effects of biological productivity growth for semi-subsistence crop and its impact on poverty reduction. The conventionally used EDM is compared with an alternative EDM that reflects more realistic assumptions for African semi-subsistence crops, such as the shape and shift of supply curve, significant margins due to high transportation costs between farmgate and consumption market, as well as between different consumption markets, and the degree of precisions of estimated structural parameters. The application to the dataset for Benin cassava farmers provides an example that the conventional EDM may significantly overestimate the total welfare gains, and may also lead to very different interpretation of how pro-poor the technology is.